Features of E-learning in language training of students in higher educational institutions - Ibrayeva, E.S. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
This article considers some of the major questions about access and accessibility, advantages and disadvantages of using e-books and online learning. The author discussed the way of designing resources for teachers, some requirements for teachers in their using or making e-books have been revealed. The modes of operation of electronic textbooks were presented in the article. As a result, important considerations were identified for the design and facilitation of electronic books.
Жоғары оқу орны студенттерінің тілдік дайындығында электронды оқытудың ерекшеліктері
Особенности электронного обучения в языковой подготовке студентов высших учебных заведений
Keywords: e-learning; language training; teaching language; language in non-linguistic institutions; higher educational institutions; designing and using e-book; e-books in language lessons; functions of e-books; correlation between students and e-books; electronic textbooks